Perspectives on human trafficking and modern forms of slavery - Kara, Siddharth (2017)
Migration, technology, law, and measurement are each among the most topical areas of enquiry in the global human trafficking field, with much work remaining to be done in these and other areas. Beneath these particular intersections lies a crucial truth-slavery is a global business that thrives on the callous exploitation of the labor activity of a vast and highly vulnerable subclass of people whose brutalization is tacitly accepted by every participant in the global economy, from corporations to consumers. I am deeply gratified to edit Social Inclusion's second issue on human trafficking and modern slavery. The level of scholarly interest in these topics continues to grow, and in this issue the authors explore some of the most pressing manifestations of human trafficking around the world.